Preoperative Folate Receptor-Positive Circulating Tumor Cells Are Associated With Occult Peritoneal Metastasis and Early Recurrence in Gastric Cancer Patients: A Prospective Cohort Study - Zeng, Ci Dian Dan; Jin, Cheng Cheng; Gao, Chun; Xiao, Ai Tang; Tong, Yi Xin; Zhang, Sheng (Frontiers in Oncology, 2022)
Background: The aim of this study is to explore the clinical feasibility of detecting folate receptor positive circulating tumor cells (FR+ CTCs) for predicting peritoneal metastasis and short-term outcome in gastric cancer patients. Methods: This is a prospective, single-center observational study. We applied ligand-targeted enzyme-linked polymerization method to detect preoperative FR+ CTCs level in peripheral blood. We evaluated the diagnostic value of FR+ CTCs and other biomarkers in predicting peritoneal metastasis. Prognostic factors for recurrence free survival were investigated in univariate and multivariate analysis. Results: A total of 132 patients with gastric cancer and 9 patients with benign disease were recruited. Gastric cancer patients had a significant higher CTCs level compared to patients with benign disease (p<0.01). Combined model including CTCs level and other biomarkers presented high sensitivity (100%) and moderate specificity (59.3%) in predicting peritoneal metastasis. Univariate analysis revealed that decreased serum prealbumin, decreased peripheral lymphocyte count, FR+ CTCs, CEA, CA19-9 and lymph node metastasis were significantly associated with shorter RFS. FR+ CTCs level (≥12.6 FU/3mL, HR=6.957, p=0.005) and CA19-9 (>34ng/mL, HR=3.855, p=0.037) were independent prognostic factors in multivariate analysis. Conclusions: Our findings for the first time suggested the diagnostic value of preoperative CTCs level in predicting peritoneal metastasis in gastric cancer. Moreover, FR+ CTCs level could be a novel and promising prognostic factor for recurrence of gastric cancer patients underwent surgery.